Quantitative gait analysis after bilateral total knee arthroplasty with two different systems within each subject - Kramers-de Quervain, Inès A.; Stüssi, Edgar; Müller, Roland; Drobny, Tomas; Munzinger, Urs; Gschwend, Norbert (The Journal of arthroplasty, 1997)
The functional behavior of two kinematically different knee arthroplasty systems within each subject was studied by gait analysis (three-dimensional kinematics, kinetics, dynamic electromyography) in five elderly patients, 2 to 5 years after bilateral surgery. Clinical results were good, yet gait velocity was reduced (range, 0.57–1.1 m/s), with a shortened stride length and a decreased duration of single-limb stance in all subjects. Force plate recordings revealed an undynamic gait with slow loading, reduced modulation of the vertical forces, and poor fore/aft shears. Sagittal plane knee motion during gait was reduced in all subjects, with trunk and pelvic compensation patterns for foot clearance. Muscle activity around the knee was prolonged bilaterally, with activity modulation related to the motion pattern. Although the stride parameters were quite symmetric, there was a marked asymmetry of the motion pattern, with a side-to-side difference of peak knee flexion during stance and swing phase of up to 15°. This finding, however, was not clearly related to the type of prosthesis. Even within one subject, significant side-to-side variability may persist, which leads to asymmetry of the motion pattern, unrelated to the kinematic design of the implant. Other factors, such as the patella-extensor mechanism, ligament balancing, leg-length discrepancy, proprioception, continuation of a preoperative habit, or a contralateral influence, may explain part of the asymmetry seen in these subjects.